2020
DOI: 10.2196/17373
|View full text |Cite
|
Sign up to set email alerts
|

A Companion App to Support Rheumatology Patients Treated with Certolizumab Pegol: Results From a Usability Study

Abstract: Background Certolizumab pegol (CZP) is an anti-tumor necrosis factor drug approved for the treatment of multiple moderate to severe chronic inflammatory diseases. In the European Union, CZP is approved for administration by subcutaneous self-injection using a prefilled syringe, prefilled pen, or reusable electromechanical auto-injector (electronic device). CimplyMe is a companion app for use alongside CZP self-injection devices, designed to support CZP-treated patients self-managing their treatment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, Apps facilitate additional real-time, time-stamped, and long-term systematic patient-centered data collection and they might serve modern management strategies in the rigid health care systems in the next years [ 37 39 ]. A similar approach has been used with electronic diaries in clinical trials to transmit self-measured clinical parameters, and furthermore, diaries on smartphones have been reported to be convenient for users [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Apps facilitate additional real-time, time-stamped, and long-term systematic patient-centered data collection and they might serve modern management strategies in the rigid health care systems in the next years [ 37 39 ]. A similar approach has been used with electronic diaries in clinical trials to transmit self-measured clinical parameters, and furthermore, diaries on smartphones have been reported to be convenient for users [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the medical context, apps are typically used for quantified self-reported data, self-management programs (e.g., for maternal health behaviour and maternal and infant health), companion apps, or as apps for other interventions (e.g., nutrition and smoking cessation) (30)(31)(32). Although it has recently been reported that medical app use in patients with rheumatic disease in Germany is quite low, more than 97% of the patients conveyed that they would consent to share their mobile app data for research purposes (33).…”
Section: Discussionmentioning
confidence: 99%
“…Expanding beyond this includes integrated sensors and apps enabling drugs to aid in chronic disease management, which can collect a variety of data from general adherence to pharmacokinetic and pharmacodynamic data that could better inform patients and their providers about usage behaviors to optimize drug adherence and treatment [9,42,43]. The next step will be fully connected DDCPs dispensed from the pharmacy, which has been seen with bioingestible sensors in oral medications and connected inhalers [44,45]. Both innovators and strategics have achieved limited product commercialization and have not yet fully explored how user error could impact collected data in chronic disease management [46].…”
Section: Key Themes Of Biopharma's Digital Health Maturitymentioning
confidence: 99%